Pengaruh Organizational Justice terhadap Komitmen Organisasi pada Karyawan Produksi di PT X - Fakhrunnisa Raudatul Rahman; Lisa Widawati; Ayu Tuty Utami (Bandung Conference Series: Psychology Science, 2022)
Abstract. During the pandemic, manufacturing companies experienced a decline in growth which resulted in many employees being laid off. Although at the end of the pandemic manufacturing companies rose again, but there has been no increase in the number of employees, it is important to maintain employee commitment, one of which is by looking at the role of organizational justice in manufacturing companies. The purpose of this study was to determine the effect of organizational justice dimensions on organizational commitment. The research hypothesis is that there is a positive and significant effect of organizational justice on organizational commitment. Participants in the study were employees of the production department at PT X as many as 60 employees. The measuring instrument used is the Organizational Justice Scale (OJS) belonging to Colquitt (2005) which was adapted by Wahyu Anggoro (2020) and the Organizational Commitment Questionnaire (OCQ) from Mowday, Steers, and Porter (1979) which was adapted by Tri Muji Ingarianti ( 2015). Analysis of the data used in this study is multiple linear regression analysis. The results of the study stated that organizational justice has a positive and significant effect on organizational commitment by 30.4%. All dimensions of organizational justice have a positive influence on organizational commitment with the most significant dimension being distributive justice, which is 70%. Abstrak. Pada masa pandemi perusahaan manufaktur mengalami penurunan pertumbuhan yang mengakibatkan banyak karyawan yang di PHK. Meskipun pada akhir pandemi perusahaan manufaktur kembali bangkit, namun belum ada peningkatan jumlah karyawan maka penting untuk mempertahankan komitmen karyawan tersebut salah satunya dengan melihat peranan organizational justice pada perusahaan manufaktur. Tujuan dari penelitian ini adalah mengetahui pengaruh dimensi organizational justice terhadap komitmen organisasi. Hipotesis penelitian adalah terdapat pengaruh positif dan signifikan dari organizational justice terhadap komitmen organisasi. Partisipan dalam penelitian adalah karyawan departemen produksi di PT X sebanyak 60 karyawan. Alat ukur yang digunakan adalah Organizational Justice Scale (OJS) milik Colquitt (2005) yang diadaptasi oleh Wahyu Anggoro (2020) dan alat ukur Organizational Commitment Questionnaire (OCQ) dari Mowday, Steers, dan Porter (1979) yang diadaptasi oleh Tri Muji Ingarianti (2015). Analisis data yang digunakan dalam penelitian adalah analisis regresi linear berganda. Hasil dari penelitian menyatakan organizational justice berpengaruh positif dan signifikan terhadap komitmen organisasi sebesar 30,4%. Seluruh dimensi organizational justice memiliki pengaruh positif terhadap komitmen organisasi dengan dimensi yang paling berpengaruh secara signifikan ialah dsitributive justice yakni sebesar 70%.